Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1198671856 species occurrences available in GBIF matching the query: { "and" : [ "OccurrenceStatus is Present", "Year 2000-2020" ] } The dataset includes 1198671856 records from 19977 constituent datasets: 67 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 ?m. 1285 records from Suivi des aires marines prot?g?es de Moorea - Invert?br?s benthiques. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture ? Paris. 21 records from Riedkanal B?tzingen. 1 records from New record of the genus Baetiella U?no, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 1 records from The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae). 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 1 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 26 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 54 records from Aves marinas del atol?n Albuquerque durante la Expedici?n Seaflower 2018 - Proyecto Colombia BIO. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 1144 records from MEXU/Leguminosae. 6 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 160 records from Waldst?ck Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 15 records from Inventaire des mammif?res du Parc de la Haute-?le (93). 52 records from Distribution of Aureoboletus projectellus in Europe. 445 records from Enrichment metagenome. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 235 records from Estimaci?n de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 23 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2138 records from DBG Physaria bellii Demographic Monitoring. 13975 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planct?nicas m?s frecuentes en el Golfo de California. 1047787 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 22888 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 9 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 6191 records from marine sediment metagenome Metagenome. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunci?n, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crust?ceos). 637 records from Colecci?n de macroalgas de la costa Argentina (IADO-UNS-CONICET). 3752 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 2396 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 12273 records from Invasive Plant Atlas of the MidSouth (IPAMS). 16 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1729 records from Estudio flor?stico de los bosques mes?filos de la Sierra Mazateca de Oaxaca, M?xico. 371 records from Bannwald Burghauser Forst. 1361 records from C?digos de barras de la vida en peces y zooplancton de M?xico. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 5 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 43 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 20500 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Donn?es 2016 P?lobate brun Comit? D?partemental de Protection de la Nature et de l'Environnement. 5663 records from Fitoplancton de la provincia oce?nica del mar Caribe colombiano. Diez a?os de historia. 3 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 6 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 8 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 86 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 2 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1512 records from ZUEC-OPH - Cole??o de Ophiuroidea do Museu de Zoologia da UNICAMP. 393 records from Analysis of plasmidome of high-altitude lakes from the Andean Puna. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from Loricifera - SMF. 22 records from COA Bird Collection (Arctos). 3 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 47 records from Bryophyte specimens of The Nagoya University Museum. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 7465 records from University of Guam Insect Collection. 833 records from Plant species from the sacred and community forests of Mono departement. 169063 records from KTP Ring Data. 4 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 151 records from Monocotiled?neas del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 584 records from Colecci?n Ornitol?gica-Museo de Historia Natural Unillanos. 174 records from Artenvielfalt des "Gr?nen Klassenzimmers". 4 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 5 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Donn?es d'observation opportunistes collect?es durant la campagne de pr?l?vements s?dimentaires SHELL/CREOCEAN en Guyane fran?aise en 2013. Shell Exploration and Production France. 2152 records from Arbeitsgemeinschaft Heuschrecken ?sterreichs. 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 2596 records from Museu de Ci?ncies Naturals de Barcelona: BGJBB. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 10742 records from Inventario flor?stico y entomofaun?stico en tres objetos de conservaci?n ecosist?micos en las zonas n?cleo de las reservas estatales de Balam-k? y Balam-kin, Campeche (Plantas). 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from Brown University Herbarium. 638 records from UWIZM Molluscs. 1824 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 1 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 29 records from UWIZM Anoles. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 6 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carri?re from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 210 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 2 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 586 records from Inventario taxon?mico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 30 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 325 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 5 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 167 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 62 records from Distribuci?n hist?rica, prospecci?n actual y ?reas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, M?xico. 12554 records from Microbial community in marine sediments. 18 records from Naturtag. 45 records from donn?es esp?ces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 105 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 2330 records from Herbier Louis-Marie (QFA) - Collection de lichens. 143459 records from Plant. 24 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 5 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 33 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Sch?ffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (St?l, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedici?n Seaflower 2017 proyecto Colombia BIO. 30070 records from 16S sequencing of environmental samples to test the impact of sediment source. 1607 records from MZFC/Coleccion de Aves. 1190 records from Coleopteros presentes en un proceso de restauraci?n pasiva en bosque seco tropical. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 46 records from DMNS Egg Collection (Arctos). 150 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 360 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 76 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 358 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 83803 records from Florida Keys Reef Visual Census 2014. 11 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 132 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 4174 records from Overv?king av ?pen grunnlendt kalkmark i Oslofjordomr?det. 529 records from Collection de longicornes et autres col?opt?res saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 26416 records from Herbarium Universitatis Daugavpiliensis. 125 records from Universidad del Valle de Guatemala - Colecci?n de Artr?podos. 1 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colecci?n Zool?gica Universidad del Tolima (CZUT) - Ar?cnidos. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 971 records from Vascular Plants from Praia da Vit?ria (Terceira, Azores, Portugal). 14487 records from An?lisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos hist?ricos y ecol?gicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1863 records from Plecoptera. 2 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 6 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 2 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 7 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 6 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 92 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 11 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 30 records from NZCS Brownsberg Nature Park Monitoring. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 52472 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 19 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 120 records from BIRDRACE The early birds. 2018 records from Donn?es odonates collect?es par le CEN Aquitaine entre 1995 et 2015. 652 records from RECORD Orthoptera Data. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 1 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 1151 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 485 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 1711 records from Herpetofauna de la regi?n marina prioritaria Corredor Puerto Madero, Chiapas, M?xico. 1989 records from Upper Silesian Museum, Bird Observations. 51 records from ISM Ichthyology Collection. 1080 records from Donn?es naturalistes de Quentin ROME. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 211 records from SEWBReC Springtails and allies (South East Wales). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 14287 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgel?nde. 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 2675 records from National Museum of Natural Science. 23 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 1293 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 20 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relaci?n con actividades antr?picas (amenazas) presentes en el Parque Nacional Natural Tatam? y su ?rea de influencia.. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 250 records from Agencement temporel des populations et des peuplements d'invert?br?s benthiques. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 111 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 71 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 147 records from Donn?es de la naturaliste Laurence Beauchamp. 6 records from Collections ichtyologiques et herp?tologiques (BOUM). 9059 records from Donn?es naturalistes de Bruno OGER. 3886 records from Colecci?n de mariposas del Museo de Entomolog?a de la Universidad del Valle. 8 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3 records from First record of the genus Tanaostigma (Hymenoptera? Chalcidoidea? Tanaostigmatidae) from the Afrotropical region with description of three new species. 19 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 24 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 9 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 581 records from Floristic records in the Moscow and Novgorod regions. 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 786 records from Weber State University Herbarium. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 90 records from Donn?es du/de la naturaliste Le baron Gaetan provenant de la base de donn?e du SINP ?le-de-France CETTIA. 875 records from Caracterizaci?n biol?gica de la ventana de biodiversidad Montes de Mar?a, Municipio de Colos?, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19339 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 4682 records from MCP-Aves - Cole??o de Aves. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 35 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 31 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 3 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 100 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 147 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 ?m. 1 records from LISU Herbario Angola. 4687 records from nhmc_ob_2019. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 67 records from Bird specimens of Saitama Museum of Natural History. 30 records from orthopteracollections-nhmj-ioj. 442 records from CNAC/Coleccion Nacional de Acaros. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 11111 records from Collections of Bioclass, school #179, Moscow. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 2226 records from pyrosequencing Raw sequence reads of deep-sea Archaea. 314 records from Mycology collection, Norwegian Forest and Landscape Institute. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 24 records from RNF - Donn?es de la R?serve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 18 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Gu?rin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mam?feros, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedici?n cient?fica en la ventana Mesay en el sector sur del Parque Nacional Natural Serran?a de Chiribiquete. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 62 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 42 records from Inventaire des Octocoralliaires des fonds s?dimentaires de la r?gion ni?oise. 1477 records from Inventaire des esp?ces v?g?tales productives dans les Syst?mes Agro-forestiers aux alentours de la For?t class?e de Ziama en Guin?e Foresti?re (BID-AF2015-0066-REG). 8 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 9 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 31656 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Herbario). 38 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 5 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 3 records from Notes on the taxonomy of some ? Astaena ? species described by Burmeister (Coleoptera: Scarabaeidae: Melolonthinae). 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 22771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajar?-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 78 records from Donn?es de la naturaliste Anna Even. 816 records from Esp?ces v?getales sur sable roux du fourr? de Ranobe, PK 32 Toliara. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 2 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 14 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 4 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 95 records from Kystfuruskoger i Tysnes og Fusa. 52 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avan?ats de Blanes, Macroinvertebrados Limno. 940 records from Modelaci?n de la distribuci?n geogr?fica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 39 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 43143 records from Syst?me d?Information R?gional sur la Faune et la Flore - FNE Centre-Val de Loire - Donn?es 2016. 68 records from Streuobstwiese. 3551 records from SIM-Fungal records compiled by Joan Mont?n. 4 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 122815 records from Western Australian Museum provider for OZCAM. 7 records from Colecci?n de mam?feros voladores y no voladores de la Universidad de Nari?o. 82 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 247 records from Flora vascular y no vascular: expedici?n Cuenca Media del r?o Chicamocha - Proyecto Boyac? BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1174742 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 29546 records from NRW Regional Data: South East Wales Non-sensitive species. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 798 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 15771 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herb?rio Virtual REFLORA. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris ?ur?i?. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldst?ck am Schullandheim Bad Bederkesa. 10 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 334 records from Aves de la expedici?n en el p?ramo de Bijagual, Boyac? - Proyecto Boyac? BIO. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Donn?es naturalistes d'Olivier DELZONS. 1552 records from Naturalis Biodiversity Center (NL) - Diptera. 72 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 164 records from Schulhof Gymnasium H?rth Bonnstrasse. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartem?wen. 538 records from Composici?n flor?stica y estructura de una parcela permanente en bosques h?medos tropicales del municipio de Pie de Pepe, Choc?. 2 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1575 records from NatureMap Calcrete Survey. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 136 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 2392 records from Elaboration de table de tarif de cubage multisp?cifique (I). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of ? tridenticulati ? and ? bidenticulati ? groups from Brazilian Amazon. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 97 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 63 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 224 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 16 records from Insect Collections of Okomu National Park- Nigeria. 84364 records from University of Minnesota Insect Collection. 135077 records from ARABEL - Arachnologia Belgica. 2330 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 4758 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 8940 records from Wolli Creek Preservation Society Bird Survey. 63 records from Inventaire des esp?ces v?g?tales de la vall?e de Gounti Y?na (Niamey). 322 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 13 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet M?chelholz (M?cheln). 166 records from Wiese am Waldrand (Gurtweil). 2 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 12 records from Gastropod Specimens of the Yamagata Prefectural Museum. 2 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 5 records from UWYMV Herpetology Collection (Arctos). 248 records from Atlas des Hym?nopt?res Pompilidae du Massif armoricain et des d?partements voisins : prospections 2018. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 1902 records from Midden-Limburg Fish Ponds Survey. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 38567 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 801 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mam?feros de los bosques montanos del Oriente Antioque?o, Ca??n del r?o Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 6 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1226 records from Plant specimens of Bihoro Museum. 895 records from Geometridae de France m?tropolitaine. 238 records from Vegetaci?n asociada a la ci?naga de Bete, municipio del Medio Atrato, Choc? 2008. 57 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 3361 records from Leicestershire and Rutland Aculeate Records. 9 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 14 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16618 records from Suivi Temporel des Libellules (STELI). 55 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 39 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bol?var 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 1143 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from Reptilia ZMK. 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucat?n Peninsula. 806 records from Diversity of Spiders from Azorean Trails. 70 records from Ensemble des donn?es Orthopt?res. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 4 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 18 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 6 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 13868 records from Donn?es faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-V?gel (VFV). 82 records from Donn?es du/de la naturaliste Swoszowski Florie provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 4348 records from NE Scotland fish records 1800-2010. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Ar?cnidos - Miri?podos de la expedici?n al R?o Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 4 records from bmhs_weatherheadshell_collection. 6 records from S?chsische Schweiz (Pfaffenstein). 578 records from Conservaci?n de la tortuga caguama del Pac?fico (Caretta caretta): protecci?n dentro del h?bitat cr?tico de alimentaci?n y desarrollo en Baja California Sur. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 5 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 12931 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 4 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 4335 records from R?seau de surveillance Polynesia Mana - Peuplements de poissons. 1 records from Living Cirripedia. 9 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 1 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 6695 records from Amundsen Gulf Overwintering Eukaryote Community. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 31 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 222 records from Land and freshwater molluscs of Northern Spain. 1 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 3753 records from Donn?es naturalistes de Charlotte PICARD. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 17349 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 76 records from Donn?es du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 5873 records from Entomology Collection at the Natural History Museum of Utah. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 1392 records from Colecci?n de Fabales del Museo Bot?nico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 40 records from makran-chabahar-arthropods. 1 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 72104 records from ALCB - Herb?rio Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 4716 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 99467 records from Fish specimens of Kagoshima University Museum. 157 records from UTEP Invertebrates (Arctos). 8 records from Diptera Collection of Museum and Institute of Zoology PAS. 85 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leit?o, 1929 (Araneae, Thomisidae). 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Cal?n y La Osa. Municipios de San Francisco y Sons?n-Antioquia.. 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 21 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 292 records from Monitoreo y recolecci?n de la diversidad de razas de ma?z criollo en la regi?n de la Huasteca en M?xico para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 6 records from Herbario MAIA, colecci?n Flora Forestal del INIA-CIFOR. 140 records from Foto trampeo al interior de las ?reas del Banco de H?bitat del Meta de Terrasos. 258354 records from MGYS00005313. 2 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 3113 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des donn?es Odonates. 317 records from Diversit? et distribution de quelques esp?ces de plantes agroforesti?res au B?nin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), esp?ce calcicole end?mique de la Polyn?sie fran?aise, d?crite de l?atoll soulev? de Niau (Tuamotu). 26 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2080 records from Modelos predictivos de distribuci?n geogr?fica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Donn?es du/de la naturaliste Chevreau David provenant de la base de donn?e du SINP ?le-de-France CETTIA. 62 records from Base de datos de las especies maderables del g?nero Dalbergia en M?xico, registros del Herbario Nacional de M?xico (MEXU). 9 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art?n Vielfalt im Kinderwald. 137 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservaci?n Guanacaste, Costa Rica. 50 records from Herpetofauna de la expedici?n Pisba - Proyecto Boyac? BIO UPTC. 19 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 460 records from Invasive Non-Native Species, Outer Hebrides. 36977 records from Phase 2 Lowland Grassland Survey of Wales. 1883 records from Naturalis Biodiversity Center (NL) - Crustacea. 11 records from Danish Ants (Formicidae). 43 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 559 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 899040 records from CLICNAT Base de donn?es naturaliste picarde g?r?e par Picardie Nature. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 263058 records from DATAVES. 23 records from Herpetofauna asociada a la cuenca del r?o Quito - Choc?, 2014. 415 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3187 records from The Broward College Insect Collection. 278 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioque?o, Ca??n del r?o Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 20 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 9657 records from Ecosph?re_2017_12_18. 642 records from An?lisis de la biodiversidad y servicios ecosist?micos para su aplicaci?n en la toma de decisiones en el departamento de Boyac?/Boyac? Bio-Flora El Consuelo. 10 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2811 records from Actualizaci?n y enriquecimiento de las bases de datos del proyecto de evaluaci?n y an?lisis geogr?fico de la diversidad faun?stica de Chiapas. 688 records from Isle of Wight non-native invasive species. 7249 records from Odonata records from RSPB Reserves 1970-2009. 857 records from Donn?es suppl?mentaires Atlas des Mammif?res marins. 53 records from Donn?es du/de la naturaliste Dubois Yves provenant de la base de donn?e du SINP ?le-de-France CETTIA. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro J?nano. 26389 records from Protist Diversity in the East China Sea. 120 records from Donn?es esp?ces - Expertise IPE 79. 1204798 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2582 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2826 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 153 records from South American Antarctic Marine Biodiversity Literature. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 81 records from M?tropole_Nice_C?te_d'Azur_2017_12_18. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 308 records from Naturmilj? Bergensbanen 2015 (project number 616033). 1930 records from Donn?es de la naturaliste Lemoine Delphine provenant de la base de donn?e du SINP ?le-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 212 records from Modelaci?n de la distribuci?n y abundancia de las subespecies de venado cola blanca en M?xico: implicaciones de conservaci?n y manejo. 7777 records from The reptiles and amphibians collection (RA) of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 6441 records from NE Scotland other invertebrate records 1800-2010. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 25 records from Base de donn?es en ligne d'observations naturalistes de mammif?res marins. GEPOG & LPO. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, M?xico: New species, new geographical records, and checklist. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Donn?es opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 24 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 24 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 14463 records from Donn?es Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 285 records from Donn?es du/de la naturaliste Cousin Richard provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 67 records from ZUEC-ECH - Cole??o de Echinoidea do Museu de Zoologia da UNICAMP. 1284 records from Records of Halicarcinus planatus at sub-Antarctic regions. 11 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis H?bner (Lepidoptera: Tortricidae). 1799 records from Herbier National de Guin?e (HNG). 4 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 459 records from EDIT - ATBI in Gemer area (Slovakia). 20009 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 596 records from Colecci?n de Herpetolog?a de la Universidad del Quind?o (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 58 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 6 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 150 records from AKG-Gel?nde (Bensheim). 2 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 3820 records from WOLL AVH data. 2 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 1381 records from Respaldo de las colecciones de tejidos del Museo de Zoolog?a, Departamento de Biolog?a Evolutiva, Facultad de Ciencias, UNAM (Aves). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 24 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 984 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2240 records from Donn?es de la R?serve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donn?e du SINP ?le-de-France CETTIA. 15788 records from Colecci?n de Peces del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P). 37 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 93 records from Caddisflies (Insecta: Trichoptera) from Maranh?o State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 3079 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herb?rio Virtual REFLORA. 1 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 1 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 210 records from Lebensraum Gesamtschule (Langerwehe). 2 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 2494 records from Donn?es des collections d'algues du MNHN. 4579 records from SP-Algae - Herb?rio do Estado "Maria Eneyda P. Kaufmann Fidalgo - Cole??o de Algas. 577 records from Col?opt?res Silphid?s du d?partement du Loiret. 80 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 1 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 200891 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammif?res marins Guadeloupe Antilles fran?aises (AET). Suppl?ments. 118 records from Observation des insectes sur le territoire de la M?tropole Rouen Normandie. 5 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 177 records from Tejidos colectados en la caracterizaci?n bi?tica para la conservaci?n de especies amenazadas en el ?rea de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 1 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 27 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 12 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 47708 records from Insects, Outer Hebrides. 1 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'int?r?t communautaire. 168 records from Restauraci?n de flora y repoblamiento de fauna nativa en 1,000 hect?reas para el restablecimiento del corredor biol?gico costero en la Laguna Madre, Tamaulipas. 372 records from Donn?es de la collection de Hubert Piguet - Famille des Elateridae. 7114 records from BioGIS - Vascular plants - Israeli Gene Bank. 2418 records from Flora de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 8 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 21 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 12608 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 409 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7839 records from Inventario flor?stico de la regi?n Calakmul-parte baja de la regi?n Lacandona (Cuenca alta del Usumacinta y Marqu?s de Comillas). 1 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 493 records from Collection Trichoptera - SMF. 12 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 117 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 2544 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 2808 records from Natura 2000 Vall?e de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 6723 records from Colecci?n de insectos agr?colas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 714 records from Museu Valenci? d?Hist?ria Natural - Fundaci?n Entomol?gica Torres Sala: FETS. 13 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 76 records from BIRDRACE Nachtigallen. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Donn?es de Midi-Pyr?n?es transmises par Pascal Peyrache.. 4 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 13 records from Donn?es naturalistes de TH?VENOT Jessica. 35084 records from Inventaire de la flore de Lot-et-Garonne 2017. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 81 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 5 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ? Piton de la Fournaise?, in R?union Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 47 records from Distribuci?n de la Nutria (Lontra longicaudis) en la cuenca baja del r?o Sin? en el departamento de C?rdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 39 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (S?o Francisco), Brazil. 101 records from Donn?es naturalistes de LE GLOANEC Vincent. 5 records from MSUM Ichthyology and Herpetology Collections. 401 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 3 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 3196 records from ERBG AVH data. 49795 records from CABI Africa Invasive and Alien Species data. 30889 records from River Biologists' Database (EPA). 4 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 5 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 230 records from Biometr?a peces Parque Nacional Natural La Paya. 55 records from Great Eastern Ranges - Slopes to Summit. 23562 records from Tiroler Landesmuseum Ferdinandeum. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 15497 records from Arizona State University Hasbrouck Insect Collection. 2536 records from Invasive Alien Species Occurrence in Ghana. 1 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaun?stico de los humedales de Puerto Morelos, Quintana Roo. 1737 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetol?gica Chetumal). 124 records from Birdrace-Die_Ackerm?nnchen-Schalm-Eder-Kreis. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 32 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1123 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 7 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 15 records from Esp?ces envahissantes de la Guin?e foresti?re extraites dans la base de donn?es de CRRA S?r?dou Macenta, IRAG.. 457 records from Helmintos par?sitos de peces dulceacu?colas de cuencas hidrol?gicas del Centro-Norte de M?xico (Durango). 57451 records from MDFRC macroinvertebrate survey. 136 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 128 records from Inventaire des reptiles 2014. 1 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 583 records from MoJ BioBlitz August 2018. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 37989 records from Diversidad y din?mica del fitoplancton marino en la bah?a de Acapulco, Guerrero. 34 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 8 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 9 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 20440 records from Inventaire de la flore de Charente-Maritime 2017. 70 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des esp?ces v?g?tales du sous bois des plantations de Teck de la for?t naturelle de la Lama. 99 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bou?ek. 61 records from Shrews of Poland. 5599 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 10939 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 85 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 146 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 31 records from STELI 2015 Saint-P?e-sur-Nivelle (64) par l'association EcoGIS. 63 records from UNIVATES - Cole??o de Ornitologia do Museu de Ci?ncias Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 29876 records from European Moth Nights. 172 records from Donn?es du/de la naturaliste Roquinarc'h Oc?ane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 26 records from Inventaire des Crustac?s D?capodes de France m?tropolitaine. Donn?es du compte CardObs 1113. 6779 records from Donn?es du naturaliste MIGUET Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 570 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 68483 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 661 records from Etude floristique de la for?t mar?cageuse de Lokoli au B?nin. 84 records from Marine algal (seaweed) flora of S?o Jorge Island, Azores. 1036 records from BUND - Dassower See (L?beck/Dassow). 49732 records from Donn?es naturalistes de Monsieur Fran?ois FOURNIER. 352 records from Birds and plant species near Petushki town (Vladimir region). 5 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 31360 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Jeu de donn?es convention FEGVE-SPN (num?ro 2). 4 records from S?chsische Schweiz (Wehlener Gebiet). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 3 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 571 records from Cuxhavener K?stenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 1493601 records from Hatikka Observation Database. 487 records from UWYMV Bird Collection (Arctos). 752 records from Donn?es naturalistes de Monsieur JOURDE R?mi. 23849 records from inatura - Erlebnis Naturschau Dornbirn. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 3792 records from Sea water microorganisms Raw sequence reads. 1212843 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paran? basin, Brazil. 3 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 2 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Mart?nez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 238 records from Donn?es Mammif?res marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1459 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 3073 records from Insect specimen database of Atsugi City Museum. 31 records from Bulletin d'informations de l'Association fran?aise de Lich?nologie. 4901 records from Nematoda of Costa Rica (INBio). 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 30 records from Morphologische Daten von Puffinus creatopus. 2577 records from WTSWW Data: All Taxa (West Wales). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 37 records from Fichas diagn?sticas para 10 especies de anfibios y reptiles mexicanos. 319403 records from Cartograf?a de vegetaci?n a escala de detalle 1:10.000 de la masa forestal de Andaluc?a. 192 records from "Ahrschleife bei Altenahr". 80124 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 7 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 13 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Brock University Herbarium (BU). 4351 records from Whicher Scarp Flora Survey. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 10269 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 15 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 59 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 20 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 53 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 6377 records from Modernisation des ZNIEFF du PnrL. 104893 records from Tasmanian Museum and Art Gallery provider for OZCAM. 6 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 16 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 1 records from Neotropical Chvalaea Papp & F?ldv?ri (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 2 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1069 records from Marine Turtles. 83 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 49 records from Colecci?n de Ar?ceas del Jard?n Bot?nico San Jorge. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 2 records from First record of the genus Chandleriella Hlav?? (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 7 records from The species of the bee genus Centris of the ? hyptidis group ? revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 4 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 38 records from Revision of the genus Shairella Ch?j?, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 6 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2185 records from Colecci?n de Geraniales hasta Lamiales del Museo Bot?nico CORD - IMBIV. 268 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from Marine algal (seaweed) flora of Faial Island, Azores. 101 records from Naturgrundst?ck (Eutin). 34 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 166 records from donn?es araneologiques de LEENKNEGT Virginie. 103 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 5 records from Herbarium Senckenbergianum (FR) - Protista. 3 records from Colecci?n de helechos de la FML. 3 records from Zoology in the Middle East. 1924 records from Herbario virtual bosques secos de Colombia - Secci?n herbario ICESI. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 41 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 39598 records from Donn?es de l'Observatoire de la Faune de Bourgogne. 3306 records from Colecci?n Herpetol?gica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 161 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 9 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 552 records from Contribuci?n al conocimiento taxon?mico de los peces que habitan los sistemas acu?ticos de la reserva de Calakmul, Campeche. 95 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1207 records from Microbial diversity studies of Arabian Sea sediment. 4337 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 3589 records from Museu de Ci?ncies Naturals de Barcelona: MCNB-Tissue. 177 records from Echinoderms from the Seaflower Biosphere Reserve. 2 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 25 records from Colecci?n de diatomeas del Herbario "Jaime Andr?s Rodr?guez". LEB-Diatomea. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 50921 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 23889 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 14 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 562 records from Actualizaci?n de la base de datos de hongos macrosc?picos de Jalisco. 18 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 29 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 7 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 322 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 143 (N.S) n? 36 (1), 2008 - Donn?es faune. 251 records from Donn?es naturalistes d'Olivier LAURENT. 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 24220 records from Restauraci?n y conservaci?n de Isla Guadalupe. 11 records from Cole??o de Coleoptera da Universidade de Bras?lia. 416 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 22 records from Site Condition Monitoring of dragonflies on Loch a? Mhuilinn SSSI potential extension - 2016. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Br?cke / B1. 5 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 2695 records from Marie-Victorin Herbarium (MT) - Bryophytes. 27 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from C?digo de barras de ejemplares de la Colecci?n Nacional de Mam?feros del Instituto de Biolog?a, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 2747 records from Compost microbe establishment and growth in agricultural soils. 90216 records from National Benthic Inventory. 358 records from Comunidad fitoplanct?nica presente en la Bah?a de Buenaventura 2018. 111 records from BIRDRACE Die Wendeh?lse. 3 records from The genus Jeekelosoma Mauri?s, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 32 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 853 records from Utah State University, Intermountain Herbarium. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 2 records from The identity of Osteobrama cotio, and the status of ? Osteobrama serrata ? (Teleostei: Cyprinidae: Cyprininae). 14282 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 657 records from Herpetofauna de la regi?n del Mar Muerto, Oaxaca-Chiapas. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 27148 records from CAS Entomology (ENT). 181825 records from Carnet B Lorraine. 892 records from Naturalis Biodiversity Center (NL) - Pisces. 5 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 17 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 159 records from Myxomycetes collection of the University of Eastern Finland. 14 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 61810 records from Donn?es du/de la naturaliste Bottinelli Julien provenant de la base de donn?e du SINP ?le-de-France CETTIA. 352848 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 69 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 1 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 10 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 308 records from Tejidos de la expedici?n en el p?ramo de Rabanal, Boyac? - Proyecto Boyac? BIO. 9 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 1234 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 464 records from Colecci?n Ornitol?gica Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 593 records from Colecci?n de Boraginales y Brassicaless del Museo Bot?nico CORD - IMBIV. 39 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 76608 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 109 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 13 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Troms?. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 36 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 61 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1744 records from Registros Primates Neotropicales Convocatoria APC. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mam?feros del ?Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna? (Reptiles y anfibios). 36 records from Schulgel?nde Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Gl?er, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 13 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 277 records from La familia Asclepiadaceae en M?xico. 9 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 29 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 18 records from Four new species of Plega Nav?s, 1928 (Neuroptera: Mantispidae) from Mexico. 1 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 370 records from Otter survey of Ireland 2004 & 2005. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 249 records from Donn?es opportunistes produites par Alexandre RUFFONI dans le cadre de l??laboration d?un guide de d?termination des larves de pl?copt?res. 2128 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 21 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopaloc?res de France (STERF). 4 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 10 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1552 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 39 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 361 records from Donn?es de VINCENT Alexis (SAPROX). 4468 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1106 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 4 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Donn?es de la structure For?ts en Aulnoye provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 15 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 1674 records from USAC Mammals Collection. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 2 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 12 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 1592 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 3 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 833 records from Donn?es naturalistes de Bernard Lalanne-Cassou. 55 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 338 records from PSUZC-Reptile Collection. 511 records from Donn?es de collection de l'inventaire des Papillons de jour de Martinique. 20 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1923 records from BioGIS - Mammals - SPNI. 25 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Direcci?n General de Medio Natural y Pol?tica Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 20199 records from Inventaire et suivis d'esp?ces dans le Parc national des C?vennes. 856735 records from SEWBReC Birds (South East Wales). 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 807 records from ?rea Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 1036 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 4 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 5017 records from Colecci?n Entomol?gica del Programa de Biolog?a - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 28 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 389 records from MEXU/Flora de Oaxaca. 21189 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 625 records from Donn?es araign?es de Corse par Canard A., Rollard C., Villepoux O.. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 3813 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9741 records from marine sediment metagenome Raw sequence reads. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 9634639 records from Pl@ntNet automatically identified occurrences. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 97 records from Amphibiens filet/Marbotte-Ronval 2013. 38249 records from Amphibiens et Reptiles de France (Enqu?te 2). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 3161 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crust?ceos, equinodermos y peces) del Santuario Islas e Islotes de Bah?a Chamela, Jalisco, M?xico. 2795 records from Donn?es naturalistes d'Alain BERLY. 4780 records from Herps Specimens. 7170 records from Insect Collection from the Museu Nacional de Hist?ria Natural e da Ci?ncia, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 701 records from Donn?es opportunistes. 946 records from Red-throated diver national surveys in Scotland - raw data. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 8 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 989 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora end?mica y casi-end?mica de matorral costero y chaparral de la zona mediterr?nea Baja California, M?xico. 1264 records from Grand Voyeux - Suivis scientifiques. 43 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 42 records from UWIZM Cnidarians. 13 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 355 records from Colecci?n Taxon?mica Nacional de Insectos ?Luis Mar?a Murillo? (CTNI). 23559 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 17 records from Surface samples of the NW Pacific Ocean Targeted Locus (Loci). 54 records from Anfibios y reptiles de la serran?a las Quinchas, Boyac? - Proyecto Boyac? BIO. 8 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 22 records from Ahuyentamiento, rescate y reubicaci?n de fauna en el ?rea de influencia directa del proyecto Hidroel?ctrico Mulatos II. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 18 records from Cole??o de Nematoda do Museu Nacional - UFRJ. 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 6254 records from Inventory of plant species through Benin (West Africa). 1 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 13 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 486 records from Donn?es du/de la naturaliste Hasrouni Sami provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1227 records from HDCF herbarium - Universidade Federal de Santa Maria - Herb?rio Virtual REFLORA. 4 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 17 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 61 records from Mollusca Collection of Saitama Museum of Natural History. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 30 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 1 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1 records from A new species of Ninia (Serpentes: Dipsadidae) from Choc?-Magdalena biogeographical province, western Colombia. 4 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic R?o Sal? basin, Tucum?n, northwestern Argentina.. 6 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 2 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 154 records from Bosque Mes?filo de Monta?a de M?xico. 53 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 1 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1967 records from Fototrampeo de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 203 records from Aix-Marseille Universit? - MARS herbarium ? Cytogenetic data-base. 16665 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 10 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 1579 records from Actualizaci?n de la base de datos de diversidad taxon?mica de las larvas de peces de Bah?a Vizca?no. 4 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 12 records from Urban Barcode Project - Fungi. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 270 records from ACT and Southern Tablelands Weed Spotter. 41 records from ?rtzem?ndung (Stedden). 37351 records from National Stag Beetle Surveys (Great Stag Hunts). 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 3 records from Morphological and molecular evidence for a new species of the genus Panolis H?bner, [1821] (Lepidoptera: Noctuidae). 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Donn?es naturalistes de Monsieur LEFEBVRE Fran?ois. 15 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1230 records from Donn?es du naturaliste Marquet Jacques provenant de la base de donn?e du SINP ?le-de-France CETTIA. 6776 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Entomologica). 12 records from Mam?feros del municipio de Santa B?rbara, Santander - Proyecto Santander BIO. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O?Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 308485 records from Herbarium of Taiwan Forestry Research Institute. 23 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 23 records from Ackerrain Pl?nhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 968 records from Donn?es odonates. 65 records from Malawi-Histeridae-Biodiversity-Data. 2048 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 10 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe?s biodiversity hotspots. 18 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE G?tkes Erben. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 19 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 21040 records from The cryptogamy collection (PC) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 33 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 23 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 566 records from Carabidae of the European North-East of Russia. 44 records from Actualizaci?n y depuraci?n de las bases de datos de la Colecci?n Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammif?res marins Guadeloupe Antilles fran?aises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 3984 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 272 records from Inventaire malacologique des murs restaur?s en pierre s?che en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyac?. 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 1040 records from Donn?es de l'Association naturaliste d'?tude et de protection des ?cosyst?mes CAUDALIS 2015 Chiropt?res, Maculinea, Cistude d'Europe. 2225 records from Donn?es naturalistes d'Ana?s MAS. 2430 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 90 records from The Myriapoda & Onychophora collection (MY) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 65 records from Donn?es du/de la naturaliste Thibault Marie Th?r?se provenant de la base de donn?e du SINP ?le-de-France CETTIA. 18 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 1205 records from uncultured eukaryote Raw sequence reads. 5112 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 3 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 13 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 1252997 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 14 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 19 records from Two new species of Brueelia K?ler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 69 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterizaci?n Ecol?gica de la Fauna del P?ramo de Frontino o del Sol. 27 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5346 records from Sediment metagenome. 4234 records from Kherson State University herbarium (KHER), Department of Botany. 17 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 796 records from Inventaire des Col?opt?res Longicornes des Antilles fran?aises. 4699 records from Nijmegen Natural History Museum (NL) - Herbarium. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 246 records from Inventaire et regroupement de donn?es Natura 2000. 11691 records from Donn?es bibliographiques et opportunistes Mammif?res du Nord Pas-de-Calais issues du SIRF. 168839 records from Donn?es de la flore d?Alsace (SBA). 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 5 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 1 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 5 records from Pygmy grasshoppers of the genus Formosatettix Tinkham? 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 2081 records from Moluscos de la Colecci?n de Referencia de Biolog?a Marina de la Universidad del Valle (CRM-UV). 56 records from Donn?es du/de la naturaliste Goncalves Cristina provenant de la base de donn?e du SINP ?le-de-France CETTIA. 37 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 3 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 24575 records from Donn?es Mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1451 records from Conocimiento de la diversidad y distribuci?n actual del ma?z nativo y sus parientes silvestres en M?xico, segunda etapa 2008-2009 (Regi?n golfo centro). 219 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 1924 records from Caracterizaci?n de la vegetaci?n en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nari?o), como insumo para la identificaci?n de oportunidades de conservaci?n para la recuperaci?n de los servicios ecosist?micos de bosque seco. 34920 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gew?sseruntersuchung (Prien) mit Kl. 4b. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1139 records from SWECO. 4227 records from Donn?es naturalistes de Lo?c SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 28085 records from EAC - Herb?rio Prisco Bezerra. 2455 records from East Ayrshire Species Database. 100 records from Euroants. 2 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1515 records from Leif Richardson Vermont Bee Specimens. 6 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur ? ventre jaune - ?tude de r?partition. 1163 records from Collection Crustacea - ZMB. 471 records from Estudio herpetofaun?stico de la Sierra Mazateca, Oaxaca, M?xico. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 14 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 3 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 3 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 24 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 16 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 41 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 2 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 7 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 13 records from Warnowufer Gro? Klein. 2575 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 3 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 45 records from Tejidos de los ejemplares colectados en la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 3 records from Sistem?tica e historia natural de algunos anfibios y reptiles de M?xico. 39 records from BOTU-Fungi - Herb?rio Irina Delanova Gemtch?jnicov - Cole??o de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en M?xico. 1556 records from Colecci?n del Herbario de la Universidad de los Llanos. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1321 records from Leicestershire and Rutland Mature trees Inventory 2011. 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 10 records from Valentin Moser Bats. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 4 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 15 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 2 records from A new species of Hemilea Loew and two new records of Trypetini (Diptera Tephritidae: Trypetinae) from India. 384 records from "Schwarzwassertal" bei Pobershau. 2041 records from marine metagenome Targeted Locus (Loci). 1832 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Koll?sen in Norway. 123 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 1 records from A new record of the genus Orientalicesa Ko?ak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 1 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 375 records from CG04_2017_12_18. 719 records from Donn?es du/de la naturaliste CUENIN Sibylle provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 22 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1 records from Collection Ephemeroptera - SMF. 526 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 146 (N.S) n? 39 (1), 2011 - Donn?es faune. 7430 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 228 records from FBIP: Identification of polychaetes used as bait. 85060 records from Denver Museum of Nature & Science - Entomology. 8 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 15409 records from Fish Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 16359 records from Database for alien invasive plants occurrences in Germany. 5 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ? notoides? clade to a new genus, Xipholeptos n. gen.. 33 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 2970 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 13 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 8313 records from ??????????. 14 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from Strathclyde badger sett surveys 1996-2000. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapaj?s basin, Brazil. 237709 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 1928 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 1069 records from Characteristics of eukaryotic plankton community in the Coastal Waters of Rongcheng by Illumina sequencing. 12420 records from OUPR - Herb?rio "Professor Jos? Badini". 49 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 29407 records from National Biodiversity Data Bank. Observation records, 1900-2014. 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotograf?as a?reas en el parque Chingaza. 182 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 946 records from Occurrence database of bryophytes and native animals of southern Chile. 87 records from VFD-H: Heidenrod: Pferdeweide M?rth. 9306 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San crist?bal). 2 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 92 records from Nottekanal, Klasse 7 - 10. 13 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 34 records from Amoeboid protists isolated from ancient Siberian permafrost. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 13904 records from donn?es aran?ologiques de CORNIC Jean-Fran?ois. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 317 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 74 records from Donn?es esp?ces - Expertise IPE 69. 7 records from Donn?es taxonomiques et ?thologiques nouvelles sur quatre esp?ces de Cigales du Sud tha?landais (Rhynchota, Cicadoidea, Cicadidae). 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 9 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 4 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 421 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6063 records from Donn?es issues du dispositif de Biosurveillance des Retomb?es Atmosph?riques M?talliques par les Mousses (BRAMM). 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geogr?fico y el nicho ecol?gico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Aj? en Santa Marta. 848538 records from MICROBIS database. 5 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 191 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-M?nster. 6926 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos las Hermosas y Chil?-Barrag?n.. 66 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 32 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 394374 records from Swiss National Orthoptera Databank. 391 records from Vegetaci?n de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 69325 records from The Environmental Sample Collection of Spiders at the Staatliches Museum f?r Naturkunde Karlsruhe. 30091 records from BIOWIDE eDNA Fungi dataset. 2 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 15404 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 5 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 320 records from Caracterizaci?n hidrogeol?gica para el diagn?stico ambiental de alternativas del proyecto hidroel?ctrico San Bartolom? (ISAGEN y HMV).. 6 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 2 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 3795 records from Composici?n flor?stica y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 13229 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 536 records from NEW-1. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaiz? et des Oiseaux de Dan Saga. 1 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimar?es & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 17 records from Biodiversity Surveys, South-east Arnhem Land. 55 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 4 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 426 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 144 (N.S) n? 37 (2), 2009 - Donn?es faune. 120 records from Tejidos asociados al estado de conservaci?n y riesgo de extinci?n del ensamblaje de anfibios de tres p?ramos colombianos. 38 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colecci?n de Peces Dulceacu?colas of Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P), Colombia. 104 records from Wichita State University Collection. 86 records from Donn?es naturalistes de Pierre-Alexis RAULT. 198118 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 9 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 6 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 56 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 1645703 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 353 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 959 records from D?partement_du_Var_2017_12_18. 191 records from sediment microorganism Metagenome. 566 records from Vertebrados registrados durante el muestreo de tigrillos mel?nicos en el Valle del Cauca. 127 records from Wildlife Observations Bardon Hill 31.5.09. 41 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 112 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 3455 records from permafrost metagenome Targeted loci environmental. 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 12822 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 3137 records from CTD water column metabarcoding. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1182 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 91 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 25 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 8 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Igua?u National Park (Southern Brazil), including a taxonomic key and distribution data. 49 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 52190 records from Hymenoptera specimen database of Kyushu University. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 2046 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 19 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 45288 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 2 records from A new species of anole from Parque Nacional Volc?n Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 232 records from Inventaire avifaune. 22654968 records from iNaturalist Research-grade Observations. 276 records from Aunar esfuerzos y recursos t?cnicos, econ?micos y humanos con el fin de adelantar acciones de investigaci?n para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 77 records from Conservatoire Botanique Pierre Fabre. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del ca?o Teracay en el r?o Tomo, Puerto Carre?o, Vichada - Proyecto Colombia Bio. 3 records from ? new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 18 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 374 records from Super?rden Dictyoptera del Museo de Entomolog?a de la Universidad del Valle (Cali, Colombia). 2 records from Cladistic analysis and synopsis of Chloropepla St?l (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el r?o Tutunendo, Municipio de Quibd?-Choc?. 9 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 11 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 18 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 1108 records from Marine algal flora of Flores and Corvo Islands, Azores. 4 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 5 records from New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 110 records from Donn?es du R?le gris sur le territoire de la Guadeloupe. 5803 records from R?g?n?ration naturelle de ligneux du S?n?gal. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 25 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 650 records from Insectivorous Bats of Gunung Mulu National Park, Malaysia. 329 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 269 records from donn?es arachnologiques de CARR David. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 4 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 90855 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herb?rio Virtual REFLORA. 1 records from Mus?e Vert ornithology collection. 867 records from Cole??o de Ictiologia do Museu de Ci?ncias Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 3 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 812 records from Esp?ces v?g?tales inventori?es dans les formations et strates de la for?t class?e de Missahoe au Togo en 2017.. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 5401 records from Donn?es L?pidopt?res de l'Auvergne transmises par Pascal Peyrache.. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 485 records from La colecci?n briol?gica del Herbario Nacional (MEXU). Actualizaci?n 2000. 85 records from Fiocruz/CMN - Cole??o de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 261 records from Donn?es esp?ces -expertise IQE 3. 154 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 38 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 7 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 2 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 5 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 5704 records from marine sediment metagenome Raw sequence reads. 4 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 360 records from Donn?es du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 35 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 13888 records from Derek Lott Coleoptera Dataset. 2 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt des PYRENEES-ORIENTALES (66). 2821 records from JCT AVH data. 827 records from University of Tennessee Bryophyte Herbarium. 286 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2665 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 21703 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 5926 records from Likona Invertebrates. 176 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 1 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 24 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 2 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 4709 records from DBRC Hemiptera species records 1969 to 2015. 38 records from BB-Biodiversit?t a. 5 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acu?ticas nidificantes de la Comunidad Aut?noma del Pa?s Vasco. 21673 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 19 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 372 records from Dorset SW Pilot species dataset. 1879 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 4 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 1 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 307446 records from Donn?es acquises dans le cadre de l'activit? du bureau d'?tude BIOTOPE (1994 - 2013). 1 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 73 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (M?lltal, K?rnten). 95 records from Vegetaci?n vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedici?n Seaflower 2016 - Proyecto Colombia BIO. 12964 records from LPO_PACA_2017_12_18. 152 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 8 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biol?gicos CIRN-INTA). 661 records from Targeting a portion of central European spider diversity for permanent preservation. 208 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 11463 records from Liste des pays par taxon sp?cimen TOGO. 7485 records from Census of species recorded during phytosociological surveys in Benin. 6977 records from 2019_NSMK_PL_2. 775 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 3451 records from Computarizaci?n de la Colecci?n de mam?feros del Centro de Investigaciones Biol?gicas del Noroeste SC. 328 records from UCYN-A diversity in the Pacific. 3 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 12 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 3682 records from NCSM Mammals Collection. 38 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 5 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 171 records from Fungal Bioblitz in Bia?owie?a Primeval Forest at 18th Congress of European Mycologists. 79719 records from Colecci?n de Entomolog?a del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-E). 190111 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 25 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum K?ster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 9 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 9 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 4207 records from CASES2003_2004. 31 records from Registros de mam?feros de los Parques Ecol?gicos Distritales de Monta?a de Bogot?, D.C.. 55 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Xiloteca). 27435 records from Fife Nature Records Centre combined dataset. 65 records from CHAS Botany Collection (Arctos). 16 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibd? - Choc?, 2019. 8 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 120 records from Naturschutzgebiet Lochbusch-K?nigswiesen. 26 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 15 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 270 records from BIRDRACE Niederlausitz-Team. 389 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 232 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from L?nea base del medio bi?tico en los bosques dentro de la zona propuesta para Acuerdos de Conservaci?n Voluntaria en la microcuenca de la Quebrada Aguazula - Rinc?n del Soldado_Yopal. 482648 records from BioFokus. 15255 records from Anymals+plants - Citizen Science Data. 55 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 991 records from Donn?es du/de la naturaliste CARON Julien provenant de la base de donn?e du SINP ?le-de-France CETTIA. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 2461 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 246 records from CNAN/Scorpiones. 15 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 1 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 1 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 11 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 137 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 3 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mam?feros peque?os en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 58 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 16 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 169 records from Biodiversidad de los Ecosistemas Mesof?ticos de la Isla de San Andr?s. 2834 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 336 records from The Vascular Plants Collection of the University of Goettingen. 29559 records from Occurrences de vecteurs de maladies recens?es ? l'H?pital de M?nontin. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 1290 records from Flora vascular acu?tica de la cuenca del R?o Tames?. 12 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 814 records from flower availability 2008 Hainich. 5 records from Two new nematode species of the genus Tobrilus Andr?ssy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 6 records from New data on brown lacewing genus Wesmaelius Kr?ger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 9854 records from Andes to Amazon Biodiversity Program. 931 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 2 records from Donn?es naturalistes de St?phane ORIO. 60 records from Suivi botanique et entomologique pour la gestion de la port?e de RTE sur l'emprise de la RNN de Bass?e. 288 records from Inventario herpetofaun?stico del noroeste de Hidalgo. 3868 records from EDP Foz-Tua: Macrophytes ? Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 1 records from The Paleontological Collections at the Bayerische Staatssammlung f?r Pal?ontologie und Geologie. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 18 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 1 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 1066 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Vestland, Troms and Finnmark, Norway (2019). 268 records from Bri?fitos del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 2 records from CNMA/Colecci?n de Mam?feros de la Estaci?n de Biolog?a Chamela. 1386 records from Aves de fragmentos de Bosque seco en la regi?n del Caribe Colombiano. 1 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 2287 records from Jard?n Bot?nico Atl?ntico, Gij?n: JBAG. 1 records from First record of Caliscelis (Caliscelis) bonellii (L, 1807) (Hemiptera: Fulgoromorpha: Caliscelidae) from Turkey, with redescription of the species. 539 records from ?tude entomologique de la ZSC du Bois de Vaires. 1419 records from Diversity of algae in wetlands. 3837 records from Donn?es rhopaloc?res collect?es par le CEN Aquitaine entre 1970 et 2015. 241 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Donn?es sur les Opisthobranches et Planaires de Mayotte. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 523 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 72 records from Fish Fauna of Berlin. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 5 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 8 records from New and little-known crickets from Southern Guangxi, China (Orthoptera: Grylloidea: Gryllidae: Phalangopsidae; Trigonidiidae). 1353 records from Weevils of Poland. 2 records from A new species of Caligus M?ller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 19 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 688 records from Arachnida of Costa Rica (INBio). 4 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 675 records from Donn?es du naturaliste RADOGEWSKI Alain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 688 records from Ross A. Layberry, Collection. 2 records from Occurrence of some antimalarial plants from Cameroon. 14257 records from Inventaire de la flore du PNRLG 2016 (Gironde). 9 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 74 records from Birdrace_G?tkes_Schergen-Helgoland. 197 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 12 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 97 records from uncultured bacterium Targeted Locus (Loci). 2 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 7 records from Donn?es naturalistes d'Olivier VILLEPOUX. 3570 records from NCSM Non-molluscan Invertebrates Collection. 6545 records from The AAU Herbarium Database. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 4 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Newly reported genus Batracomorphus Lewis (Hemiptera: Cicadellidae: Iassinae) from Pakistan with description of a new species. 2 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 424 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 212 records from Colec??o Entomol?gica do Museu de Hist?ria Natural de Maputo. 9 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 722 records from Heritage Trees of Ireland. 200 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 1074 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Donn?es du/de la naturaliste LUPOLI ROLAND provenant de la base de donn?e du SINP ?le-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 14163 records from Herbario de la Facultad de Ciencias Biol?gicas de la Universidad Complutense de Madrid (MACB). 8 records from RISC Non-Native Species Records for Zebra Mussel. 3 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 46 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 147 (N.S) n? 40 (2), 2012 - Donn?es faune. 16 records from Revalidation and taxonomic revision of Teloneria Acz?l (Diptera, Neriidae), with description of two new species. 18 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 100 records from Donn?es d'observation d'?crevisses exotiques envahissantes en Haut de France et Normandie sur la p?riode 2014 ? 2018. 210 records from Freshwater fish records via iRecord - additional species. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 26 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 22575 records from Living plant collection of Meise Botanic Garden. 1 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20?m. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 222 records from SJRP-Fungi - Herb?rio de fungos de S?o Jos? do Rio Preto. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 1546 records from Aves de la expedici?n en lago de Tota, Boyac? - Proyecto Boyac? BIO. 3559 records from Gunma Museum of Natural History, Fungi Specimen. 2 records from Kirchenforst. 13099 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 54 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 13 records from Eight new species of Ptenidiini and Discheramocephalini (Coleoptera: Ptiliidae) from Ecuador. 15 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedici?n Seaflower 2017 - Proyecto Colombia BIO. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 259 records from Bats of Northern Peninsular Malaysia. 2 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 2 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 452 records from ZUEC-HEM - Cole??o de Hemiptera do Museu de Zoologia da UNICAMP. 330 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 59891 records from UWFC Ichthyology Collection. 7762 records from Auburn University Museum of Natural History Invertebrates. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 24 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 58 records from Mam?feros laguna El Tinije. 112 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 2593 records from DREAL_PACA_-_N2000_-_Parc_Naturel_R?gional_du_Queyras_2017_12_18. 4 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 5423 records from MPUC - Herb?rio do Museu da Pontif?cia Universidade Cat?lica do Rio Grande do Sul. 735 records from EDP Foz-Tua: Vascular Flora ? Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 558 records from ?rea Ot?n Quimbaya - Densidad poblacional valores objeto de conservaci?n Santuario de Fauna y Flora Ot?n Quimbaya, 2016. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 9410 records from CUMV Fish Collection. 3 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 732951 records from Donn?es ONF faune-flore-fonge. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 48 records from Deutsche Schule Budapest. 1463 records from Regroupement de donn?es rhopaloc?res r?colt?es sur la p?riode de 2010-2015 par Cistude Nature. 2 records from ZUEC-POP - Cole??o de Polyplacophora do Museu de Zoologia da UNICAMP. 1 records from Stenus maculifer CAMERON: eine B?chse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 13790 records from University of Tennessee Fungal Herbarium. 1882 records from University of Michigan Museum of Zoology, Division of Mollusks. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 32 records from Site Condition Monitoring of the downy willow Salix lapponum component of the Vascular Plant Assemblage interest of Skinsdale Peatlands SSSI, 2016. 19651 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos Tota-Bijagual-Mamapacha. 576 records from Flora ficol?gica de la huasteca potosina. 29851 records from Donn?es acquises via le r?seau du Conservatoire botanique national du Bassin parisien. 1307 records from Donn?es opportunistes. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 5324 records from DASSH Data Archive Centre Academic Surveys. 2 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Mus?um national d?Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 28 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 5 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 229 records from Nanticoke Harbour, ON, Canada (plankton SSU 454 sequencing). 81191 records from Dry Tortugas Reef Visual Census 2014. 3 records from New species and two new records of Erythroneurini from China (Hemiptera Cicadellidae, Typhlocybinae). 881 records from Monitoreo participativo de flora presente en Bosque Seco de los departamentos de Bolivar, Huila y La guajira. 4 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 2092 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 39164 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 144 records from MEXU/Tipos de plantas vasculares. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 12 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 6 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 210 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 146 (N.S) n? 39 (4), 2011 - Donn?es faune. 10 records from Bachpatenschaft Beeke. 462 records from Donn?es du/de la naturaliste Dodelin Beno?t provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3199 records from Estado actual, identificaci?n de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrol?gicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del r?o de La Laja. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 21 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 15 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Donn?es naturalistes de Daniel PAVON. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 15 records from Modelaje de la distribuci?n potencial de 10 especies de anfibios y reptiles en riesgo de extinci?n con escasos registros de presencia (ANONAU). 363 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 35 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 60 records from Caracterizaci?n de la fauna reptiliana asociada a la cuenca del r?o Atrato, para el estudio de su navegabilidad, Quibd? - Choc?, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 262487 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 2 records from On the Neotropical spider genus Tullgrenella Mello-Leit?o, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 1 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 2 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 6272 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 1922 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 154 records from Donn?es de la structure Philofauna provenant de la base de donn?e du SINP ?le-de-France CETTIA. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 7 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 10876 records from Cumbria Non Native Invasive Species. 1 records from A new species of Stenampyx Karsch, 1890 from East Africa (Orthoptera: Tettigoniidae, Pseudophyllinae, Phyllomimini) - evidence of a former connection of West-Central and East African forests. 35 records from Inventaire et suivi de la faune ?cras?e. 1000 records from nsmk_mm_2019. 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 11 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 176 records from Rund um den Eichwald,Schulhof Friedrich Fr?bel Gymnasium- Bad Blankenburg. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 126 records from DAR AVH data. 80713 records from England Non Native Species records 1965 to 2017. 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 2 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 222 records from L??valuation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation ? sangaredi, Bok? (CESP2016-022). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan ???????. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 858 records from Colecci?n Ornitol?gica de la Universidad Tecnol?gica del Choc?. 3178 records from Newfoundland sediment pyrosequencing. 195 records from Pedestrian mammals census in W National Park. 927 records from Oc?anopolis mammif?res marins en Bretagne 1993-2015. 12594 records from BLS Rare and Threatened Lichen Records: England. 2 records from New morphological information on Simulium wygodzinskyorum Coscar?n & Py-Daniel, 1989 (Diptera: Simuliidae). 145 records from Gronau - auf der Suche nach dem Neunauge. 4682 records from Fungal diversity in Sanya mangrove sediments, China. 95 records from Conocimiento de la diversidad y distribuci?n actual del ma?z nativo y sus parientes silvestres en M?xico (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversit? Littorale (BioLit). 19747 records from Eden Arthropod Azores Database. 5 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 2 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 1304 records from Thrips (Thysanoptera) in Norway. 2 records from A new species of Homo from the Late Pleistocene of the Philippines. 4065 records from Microbial community in permeable intertidal sediment. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementaci?n de la bioindicaci?n en el R?o Cauca - 2016. 5 records from Mammalian Specimens of the Yamagata Prefectural Museum. 81 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 62 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulid?es d'Europe. 209740 records from uncultured prokaryote Targeted loci environmental. 391 records from GEOECOLINK_2017_12_18. 52 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 28 records from UTEP Herpetology Osteology (Arctos). 21 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 125875 records from The Scottish Squirrel Database. 96 records from BIRDRACE OAG Neuwerk. 36 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 10 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 168 records from Caracterrizaci?n flor?stica del humedal La Abuelita, Municipio de Guapi-Cauca, 2018. 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 36 records from Selz (Ingelheim am Rhein). 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2594 records from Flora of Sumatra : Vascular plant collection from Batang Toru Forest deposited in ANDA Herbarium. 102 records from A Lichen Survey of the Ben Nevis Plateau. 2 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 3 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 943 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 37 records from FBIP: Baboon spider distribution records from selected South African museums. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 9957 records from Donn?es du naturaliste Tillier Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 18 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 493 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 329 records from Donn?es naturalistes de Laurent PONCET. 2 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 45 records from Colecci?n de Oligoquetos Acu?ticos de la UPV/EHU. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 1349 records from Caracterizaci?n flor?stica y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicci?n Corantioquia. 3 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de C?rdoba. 5901 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 489 records from Royal Ontario Museum Fungarium (TRTC). 170 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt du CHER (18). 44365 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 205 records from El c?digo de barras de las especies NOM-059 de mam?feros del Noroeste de M?xico. 3188 records from Butterfly_conservation_2017_12_18. 16458 records from Inventaires faune. 17 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 6613 records from Plant specimens of Horaiji-san Museum of Natural History. 22 records from Pachyrhynchus elenae Rukmane, 2016, a new synonym of Pachyrhynchus phaleratus Waterhouse, 1841 (Coleoptera: Curculionidae: Entiminae). 27 records from Laubwald Dreil?ndereck (Aachen/Vaals[NL]). 40020 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 2 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 23908 records from Donn?es bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d?indicateurs de biodiversit?. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from D?ne am Ulvenberg (Darmstadt). 4 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 17 records from Donn?es naturalistes d'Emilie WEBER. 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 30 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 1072 records from Mammals housed at MHNG, Geneva. 5 records from Two new ? Asura - like? Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 14465 records from L?yd?s Open Invasive Alien Species Observations. 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillh?tte Wettsaasen, Wiese, Hecken. 671 records from Swiss Psyllid (Hemiptera) Collections - Basel. 155 records from Donn?es du/de la naturaliste VAN DEN BRINK Sylvie provenant de la base de donn?e du SINP ?le-de-France CETTIA. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 37 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 405 records from Arctic sea-ice and sub-ice seawater raw sequence reads. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 1 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 982 records from Pilotoverv?king av dragehode Dracocephalum ruyschiana. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 38 records from UWIZM Mantodea. 1 records from A new and five rare bdelloids from Korea. 255 records from Distribuci?n actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de con?feras del estado de Oaxaca. 7 records from Review of the Oriental leafhopper genus Parafagocyba Kuoh & Hu (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China. 1 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 3555 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Taxonom?a y prospecci?n del h?bitat de las poblaciones de Bursera sect. Bullockia con especial ?nfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 221 records from donn?es bibliographiques diverses (non araign?es). 16 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atl?ntica, Brazil. 284 records from UNM Earth Sciences Collection (Arctos). 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10229 records from Exp?dition Karubenthos 2012 : inventaire des Mollusques et des Crustac?s de la Guadeloupe. 2 records from New and interesting species of the generaGalumna andPergalumna (Acari, Oribatida, Galumnidae) from the Montagne d?Ambre National Park, Madagascar. 22 records from New records of ant species from Yunnan, China. 3388 records from Caracterizaci?n biol?gica en la Serran?a de San Lucas 2015. 48 records from Survey of Plankton Diatoms in Nanren Lake. 59 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 186 records from Great Koala Count 2. 82 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 538 records from Bird specimens of Komatsu City Museum. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 13 records from Donn?es naturalistes de BRULE Herv?. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rond?nia, western Amazonia, Brazil. 135 records from Boreonemoral regnskog p? ?stsiden av Lygrespollen. 12 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 1257 records from Geotraces Raw sequence reads. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 5 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 26 records from Liste des oiseaux de BZM Belambo. 2 records from Cacoplistes (Laminogryllus) brevisparamerus sp. nov., a new species of Cachoplistinae (Orthoptera: Phalangopsidae) from Guangxi, China. 3 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 85 records from Donn?es esp?ces - Expertise IPE 123. 50 records from Beetles on polypores at 4 sites in Norway. 2441 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 19 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 11 records from Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 17398 records from NEON Biorepository Invertebrate Bycatch Collection (Archive Pooling). 154 records from Collection Crustacea - ZSRO. 11 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 53961 records from Long-Term Monitoring Network Vegetation Quadrats. 1 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 1075 records from Inventaire et suivi Rhopaloc?res. 12395 records from Donn?es naturalistes de Pierre FRAPA. 52 records from Coleccion de helechos de la FML. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 112 records from Quoll sightings register for Nth QLD. 3 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 15 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 109 records from Exkursion Ebertsheimer/Gr?nst?dter Berg. 1 records from A new species of Ischyomius from Venezuela (Coleoptera, Tenebrionoidea, Pythidae) with a revised key to world species. 61245 records from University of Florida Invertebrate Paleontology. 2 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 28690 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herb?rio Virtual REFLORA. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Donn?es naturalistes de Thibault RAMAGE. 43 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 43 records from Vogelstimmenf?hrung durch den Tiergarten. 2 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis,
Keywords: GBIF; biodiversity; species occurrences